Sosialisasi Literasi Digital bagi Siswa Sekolah Menengah Atas Negeri 3 Bukittinggi - Anita Afriani Sinulingga; Bima Jon Nanda; Putiviola Elian Nasir; Silvy Qory (Warta Pengabdian Andalas, 2021)
This community service regarding the socialization of digital literacy aims to raise awareness of the importance of digital literacy to high school (SMA) students. Digital literacy is processing and sorting information to minimize the negative impact of receiving incorrect information online. It should be filtered first, especially in the digital era and globalization, where the flow of information is so fast and easy to access due to the narrowing of space and time due to technological developments. This service activity was the growth of essential digital literacy skills for the target participants. This ability was characterized by sorting between true and false information by looking for supporting data for that information. This can be seen in the last series of activities determining which information is accurate and which is false.